(untitled) (Dimensión Empresarial, 2018)
This review article aims to analyze one of the most important elements in the software industry: the conformation of self-managed work teams and the implementation of a planning, control and development methodology of software project.For that, a literature review was made, researching journal articles, graduation projects and books, among others, to know the software industry generalities worldwide, as well as the situation in Colombia, the conformation of self-managed work teams and the agile methodologies features for planning, executing and controlling development projects. The self-managed teams’ conformation eases communication and knowledge sharing, essential elements inside the software development industry since they allow the generation of an appropriate answer in front of the changes caused by the environment. Supporting on the Scrum development methodology, value for the stakeholders is obtained and a workflow is set, guided to improve project productivity and efficiency.